Occupational injuries among craft brewery workers in Colorado - Brents, Colleen, author; Rosecrance, John, advisor; Brazile, William, committee member; Anderson, Brooke, committee member; Gibbons, Alyssa, committee member; Biegert, Jeff, committee member (Colorado State University. Libraries, 2021)
Workers at craft breweries in the U.S. are an understudied occupational cohort in a rapidly growing industry. Between 2015 and 2019, the number of craft breweries in Colorado grew 120% (Brewers Association, 2020). At the start of 2020, Colorado had more than 420 craft breweries with more than 9,100 workers. California is the only state with more craft breweries than Colorado. In the U.S., 8,000 craft breweries employed 161,000 workers (Brewers Association, 2020). As craft brewery workers produce beer through manufacturing processes, they are exposed to numerous occupational hazards that have been associated with injuries. These hazards include awkward body postures, lifting/carrying heavy loads, highly repetitive activities, sharp edges on materials and equipment, hot surfaces, and high levels of noise. According to national injury surveillance data, occupational injury rates are higher among brewery workers compared to all industries including private, state, and local government. Unfortunately, the national injury surveillance data do not differentiate between large and craft breweries. Craft breweries are substantially smaller than large industrialized breweries. An analysis of national injury data that includes all sizes of breweries may lead to erroneous perceptions of injuries affecting craft brewery workers. To date, no published studies have specifically outlined occupational hazards and injuries associated with craft brewing tasks. To effectively improve safety among craft brewery workers, it is critical that researchers and industry stakeholders have a better understanding of the occupational exposures related to injuries specific to craft brewery workers. The purpose of the present study was to characterize injuries specific to craft brewery workers and to identify their contributing factors in order to inform practitioners tasked with directing intervention resources. Researchers used data from workers' compensation to analyze injuries among Colorado craft brewery workers from 2013 to 2018. Researchers then analyzed accident narratives using the revised agent-host-environment epidemiologic model to better understand the relationship between the reported injury claim and the contributing factors to the agent, host, environment, and vehicle. Informal interviews with subject matter experts supplemented the workers' compensation analysis. Due to restrictions caused by the COVID-19 Pandemic, qualitative data were collected through virtual informal interviews with subject matter experts. Researchers developed a series of injury process models to highlight the relationship between injury characteristics and contributing factors that resulted in an injury nature. These models included information on how an injury nature was the result of an injury event when energy was transferred from the environment or vehicle to the injured workers' anatomical region. Researchers analyzed 570 claims. Results of the present study indicated that new workers experience occupational injuries, as more than 60% of claimants had less than two years of tenure at the time of injury. Among claims that incurred costs, the median total claim cost was $680 and the mean total claim cost was $2,100. Claims associated with sprains/strains incurred the highest costs per claim and the highest cumulative cost. Sprains/strains and contusions were the most frequent injury natures. The low back, hands, and fingers were the most frequently injured body parts. By analyzing accident narratives, researchers determined that injuries in craft breweries were typically associated with claimants either carrying items or performing cleaning tasks. The majority of injuries occurred in the packaging hall area of the craft brewery. Subject matter experts described how the packaging hall typically had the highest number of workers and the greatest proportion of new workers compared to other regions of the craft brewery. Contusions, lacerations, and burns affected the hands/fingers whereas sprains/strains predominately affected the low back. Sprains/strains and contusions both typically occurred in the packaging area of the craft brewery while the claimant carried an item. Lacerations typically occurred in the packaging area or kitchen. Burns typically occurred in the brewery or kitchen. Both burns and lacerations occurred while the worker performed maintenance work, cleaning activities, or food preparation tasks. Findings from this study (including the injury process models) can help guide practitioners tasked with developing interventions to reduce injuries and improve the quality of work life among craft brewery workers.
Keywords: occupational ergonomics; safety; craft brewing; workers' compensation; occupational injuries